Sistem Pendukung Keputusan dengan Analisis Pencocokan Profil untuk Pemilihan Jurusan di Perguruan Tinggi - Topan Setiawan (Jurnal Accounting Information System (AIMS), 2021)
Selection of majors that are not in accordance with the qualifications possessed by students at Senior High School Negeri 1 Garut will be one of the inhibiting factors while the student is in college. To minimize such conditions, a decision support system is needed that can analyze student profiles with the profiles of existing majors. The goal is that the majors chosen by students are in accordance with their qualifications. The profile matching method or GAP analysis is the method used in this study. With GAP analysis, the gap between student profiles and majors profiles can be identified. The smaller GAP value is higher the match level, and vice versa. Meanwhile, the recommended major that has highest recommendation value. Based on the results of research conducted on a student named Roihana Asfahani, recommended majors based on value of knowledge, skills, talents and interests in these students are majors in the psychology with a recommendation value of 16.96.